Morphological measurements of a short-toed eagle chick (Circuaeus Gallicus) during the nesting period: A study to analyze growth rates, Al-Jabal Al-Akhdar -Libya. - Younis M. Al-Zaedi; Mohammed A. Abusharya; Saleh A. Buirzayqah (Libyan Journal of Science &Technology, 2026)
This study, conducted in the Wadi Al-Naqa reserve in the Al-Jabal Al-Akhdar region of eastern Libya, monitored the morphological development of a short-toed eagle chick over five consecutive breeding seasons (2020-2024 AD). Measurements of length, width, weight, claw length, and leg length were taken using a measuring tape and an electronic scale during the nesting period and were analyzed statistically. The results revealed that the chick's growth increased significantly after 45 days post-hatching, with maximum average measurements reaching 31cm (length), 24 cm (width), 1.7 kg (weight), 2.7 cm (claw length), and 19cm (leg length). The greatest annual increase in length, width, weight, and leg length occurred in 2021, while the largest increase in claw length was recorded in 2024. A strong positive correlation was identified among all morphological characteristics. These findings provide a detailed analysis of the growth and developmental trajectory of a short-toed eagle chick.